Self-lubricating behaviours of ceramic tools in dry cutting. (9th October 2006) - Jianxin, Deng; Xuefeng, Yang; Jianhua, Liu
An in situ reaction self-lubricating ceramic tool (i.e. Al2 O3 /TiB2 ) and a self-lubricating ceramic tool with the addition of solid lubricants (i.e. Al2 O3 /TiC/CaF2 ) were produced by hot pressing. The lubricating behaviour of these self-lubricating tools in dry cutting processes were studied. It was shown that self-tribofilms, which contributed to the decrease of the friction coefficient at the tool-chip interface, were consistently formed on the tool rake surface for these self-lubricating tools. The formation process and composition of these self-tribofilms were determined and the self-lubricating mechanisms were advanced. Cutting speed was found to have a profound effect on the self-lubricating behaviours. These self-lubricating tools can be used to reduce the friction coefficient between the tool-chip interface during dry cutting.